Disaggregated estimates of output supply and input demand elasticities - Shumway, C. Richard; Villezca Becerra, Pedro A. (Estudios Económicos de El Colegio de México, 1995)
Designed for consistency with competitive theory, non-rejected simplifying assumptions and multi-stage choice, aggregate dual models are specified of Texas agricultural production. Disaggregated own- and cross-price elasticities are derived for 25 commodity supplies and six input demands. Estimated supplies and demands are largely inelastic. Outputs are mainly economic substitutes and inputs are economic complements.